Предмет:
МатематикаАвтор:
анонимВоспользовавшись формулой для производной произведения 2-х функций, получим:
А) y\' = (x^2 + 3)\' * (x^4 - 1) + (x^2 + 3) * (x^4 - 1)\' = 2x * (x^4 - 1) + 4x^3 * (x^2 + 3);
Б) y\' = (x^2 - 2)\' * (x^7 + 4) + (x^2 - 2) * (x^7 + 4)\' = 2x * (x^7 + 4) + 7x^6 * (x^2 - 2).
Автор:
sonia2pvcДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть